Emerging Role of MiR-192-5p in Human Diseases - Ren, Fu-jia; Yao, Yao; Cai, Xiao-yu; Fang, Guo-ying (Frontiers in Pharmacology, 2021)
MicroRNAs (miRNAs) are a type of small non-coding RNAs that play an essential role in numerous biological processes by regulating the post-transcriptional expression of target genes. Recent studies have demonstrated that miR-192-5p, a member of the miR-192 family, partakes in several human diseases, especially various cancers, including cancers of the lung, liver, and breast. Importantly, the levels of miR-192-5p are abundant in biofluids, including the serum and urine, and the exosomal levels of miR-192-5p in circulation can aid in the diagnosis and prognosis of various diseases, such as chronic hepatitis B (CHB) infection disease. Notably, recent studies suggest that miR-192-5p is regulated by long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs). However, there are no comprehensive overviews on the role of miR-192-5p in human diseases. This review discusses the significant studies on the role of miR-192-5p in various human diseases, with special emphasis on the diseases of the respiratory and digestive systems.